2023
DOI: 10.1063/5.0135162
|View full text |Cite
|
Sign up to set email alerts
|

Multi-peak emission of In2O3 induced by oxygen vacancy aggregation

Abstract: Oxygen vacancy is crucial to the optical properties in In[Formula: see text]O[Formula: see text], however, the single oxygen vacancy model fails to explain the observed multi-peak emission in the experiment. Herein, we have theoretically investigated the diversity of oxygen vacancy distribution, revealing the relationship between the defect configurations and the optical properties. Combining the first-principles calculations and bayesian regularized artificial neural networks, we demonstrate that the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The work function of In 2 O 3 is 5.0 eV, and the C 1s peak of In 2 O 3 can be set at 284.58 eV [37,38]. As shown in Figure 3a It is reported that the Vo in In2O3 thin films can provide electrons as shallow donors, thus UID-In2O3 thin films often contain very high background carrier concentration [41][42][43]. To evaluate the electrical properties of the In2O3 crystal film, Hall measurements are carried out and the measurement structure has been illustrated in Figure 4a.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The work function of In 2 O 3 is 5.0 eV, and the C 1s peak of In 2 O 3 can be set at 284.58 eV [37,38]. As shown in Figure 3a It is reported that the Vo in In2O3 thin films can provide electrons as shallow donors, thus UID-In2O3 thin films often contain very high background carrier concentration [41][42][43]. To evaluate the electrical properties of the In2O3 crystal film, Hall measurements are carried out and the measurement structure has been illustrated in Figure 4a.…”
Section: Resultsmentioning
confidence: 98%
“…The results are consistent with that of Hall and XPS measurements, which indicates that the reduction of the fTMIn can effectively suppress the Vo thus reduce the Id of the In2O3 PDs. It is reported that the V o in In 2 O 3 thin films can provide electrons as shallow donors, thus UID-In 2 O 3 thin films often contain very high background carrier concentration [41][42][43].…”
Section: Resultsmentioning
confidence: 99%